Moscow University professor M. S. Korelin and student movement at the Moscow University in the late 19 th century (according to the diary) - N. ILYASHENKO (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the attitude of the Moscow University Professor M. S. Korelin to the student movement. Analysis of the views of Korelin is made on the basis of nonpublished diary of Professor, which preserved in the Central State archive of Moscow. Actually Korelin considers the student activity during the period (1889—1896) of the particularly interesting from the point of view of the formation of the student movement in Russia. The author comes to the conclusion that Korelin held an active position in relations with youth, sought to get closer acquainted with the students, to find a contact with them, and common interests, to understand their environment. Using the trust part of the students he could learn more about the life and the essence of illegal student corporations. sympathizing with noble motives students fight against immorality — Korelin rejected terroristic methods of struggle. However, he believed that the unifying factor for professors and students can only be established in the scientific activity. Korelin points out that the cause of the student movement was the University Law of 1884 which made the administration of the University powerless against the student movements. The analysis of the views of Korelin allows to expand the idea of relationship between professors and students of that time, provides new information on the history of the student movement in Russia and about the history of the faculty-student relationships in the end of XIX century.